Simulating the effect of perennialized cropping systems on nitrate-N losses using the SWAT model - Wilson, Grace L.; Mulla, David J.; Jordan, Nicholas R.; Jungers, Jacob M.; Gordon, Brad A. (Frontiers in Agronomy, 2023)
SSeveral newly released crop varieties, including the perennial intermediate wheatgrass (grain marketed as Kernza®), and the winter hardy oilseed crop camelina, have been developed to provide both economic return for farmers and reduced nutrient losses from agricultural fields. Though studies have indicated that these crops could reduce nitrate-nitrogen (N) leaching, little research has been done to determine their effectiveness in reducing nitrate-N loading to surface waters at a watershed scale, or in comparing their performance to more traditional perennial crops, such as alfalfa. In this study, nitrate-N losses were predicted using the Soil and Water, Assessment Tool (SWAT) model for the Rogers Creek watershed located in south-central Minnesota, USA. Losses of nitrate-N under three perennialized cropping systems were compared to predicted losses given current cropping practices (corn (Zea mays L.) -soybean (Glycine max L. Merr.) rotation). The perennialized systems included three separate crop rotations: intermediate wheatgrass (IWG) in rotation with soybean, alfalfa in rotation with corn, and winter camelina in rotation with soybean and winter rye. Model simulation of these rotations required creation of new crop files for IWG and winter camelina within SWAT. These new crop files were validated using measured yield, biomass, and nitrate-N data. Model results show that the IWG and alfalfa rotations were particularly effective at reducing nutrient and sediment losses from agricultural areas in the watershed, but smaller reductions were also achieved with the winter camelina rotation. From model predictions, achieving regional water-quality goals of a 30% reduction in nitrate-N load from fields in the watershed required converting approximately 25, 34, or 57% of current corn-soybean area to the alfalfa, IWG, or camelina rotations, respectively.